Recuperação da dimensão vertical em pacientes com parafunção severa - Amoroso, Andressa Paschoal [UNESP]; Gennari Filho, Humberto [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Zavanelli, Adriana Cristina [UNESP] (My University, 2013)
The association between emotional stress and intense bruxism has as consequence the Temporomandibular Disorder (TMD), which is an increasingly apparent problem at the dental clinic, requiring judicious means of diagnosis and especially treatment.. Several factors, of equivalent importance, may be related to the DTM, one of them is the loss of vertical dimension of occlusion (VDO), and parafunctional habits and also the loss of stable contacts between the posterior teeth or lack thereof, which generates an increase functional anterior teeth for excessive wear or buccal and consequent.. This paper proposes using a clinical case, to present and discuss the steps for clinical diagnosis, planning and execution of oral rehabilitation with Fixed Partial Denture for restoring vertical dimension of occlusion in a patient with severe parafunction.. Oral rehabilitation of these patients should be carefully planned, respecting the functional and aesthetic aspects.. The parafunction control by monitoring the Temporomandibular Disorder is essential to the longitudinal prediction of rehabilitation performed in these types of rehabilitative treatment.

A associação entre o estresse emocional e o bruxismo intenso, tem como conseqüência a Disfunção Temporomandibular (DTM), que representa um problema cada vez mais frequente na clínica odontológica, exigindo meios criteriosos de diagnóstico e, principalmente, de tratamento.. Diversos fatores, de equivalente importância, podem estar relacionados com a DTM, um deles é a alteração da Dimensão Vertical de Oclusão (DVO), sendo os hábitos parafuncionais e também a perda de contatos estáveis entre os dentes posteriores ou ausência dos mesmos, o que gera um aumento funcional excessivo aos dentes anteriores e conseqüente desgaste ou vestibularização.. Este trabalho se propõe através de um caso clínico, a apresentar e discutir as etapas clínicas para diagnóstico, planejamento e execução da reabilitação oral com Prótese Parcial Fixa para o restabelecimento da dimensão vertical de oclusão em paciente com parafunção severa.. A reabilitação Oral destes pacientes deve ser rigorosamente planejada, respeitando os aspectos funcionais e estéticos.. O controle da parafunção mediante o acompanhamento da Disfunção Temporomandibular é essencial ao prognóstico longitudinal da reabilitação executada nestes tipos de tratamento reabilitadores.
Recovery of Vertical Dimension in patient with severe parafunction
Keywords: Oral rehabilitation; Vertical dimension; Temporomandibular disorder; Reabilitação oral; Dimensão vertical; Disfunção mandibular